FACTORS THAT INFLUENCE ENTREPRENEURIAL INTENTIONS AMONG ENTREPRENEURIAL STUDENTS IN WEST JAKARTA - Juan Daniel Christopher; Andi Wijaya (Graduate Program of Universitas Tarumanagara, 2026)
Entrepreneurship education and personality are key factors influencing an individual’s entrepreneurial intentions. This study aims to analyze the relationship between entrepreneurship education and personality on entrepreneurial intentions, with entrepreneurial motivation as a mediating variable. The research employed a quantitative approach using a survey method involving 200 students from entrepreneurship study programs at several universities. Data were collected through a Likert-scale questionnaire and analyzed using SMART-PLS 4 software. The results indicate that entrepreneurship education and personality have a positive and significant effect on entrepreneurial motivation. Furthermore, entrepreneurial motivation significantly and positively influences entrepreneurial intentions. Mediation analysis shows that entrepreneurial motivation plays a significant mediating role between entrepreneurship education and personality in shaping entrepreneurial intentions. These findings provide empirical evidence that enhancing entrepreneurship education and personality development can increase students’ entrepreneurial motivation and intentions. The study suggests the need to develop a more comprehensive entrepreneurship curriculum and personality development programs to strengthen entrepreneurial intentions among students. Theoretical and practical implications are discussed in relation to contributions to educational literature and policy. Overall, this research contributes to the theoretical understanding of factors influencing entrepreneurial intentions and offers practical insights for entrepreneurship education and human resource development in higher education.